PENGARUH KONTEN KREATIF MEDIA SOSIAL TERHADAP PELESTARIAN BAHASA LAMPUNG - Dewi Yanti; Vernia Nur Afni; Rahmat Prayogi (STKIP Pesisir Selatan, 2025)
This study aims to describe the forms of creative content on social media utilized in the preservation of Lampung language, analyze the influence of social media creative content on increasing young generation's interest in using Lampung language, and formulate effective creative content strategies for Lampung language preservation through social media. This research employs a qualitative approach with descriptive method. Data collection was conducted through observation of Lampung language content on Instagram and TikTok platforms, as well as documentation in the form of content screenshots, engagement statistics data, and supporting literature. Data were analyzed using the Miles and Huberman model through stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that creative content on social media takes the form of interactive educational content and cultural content packaged in short videos with attractive visual techniques. Such content has a significant influence on increasing awareness and cultural pride of the young generation toward Lampung language, as evidenced by positive responses in the comment sections. Effective strategies that can be implemented include integration of trends and locality, collaboration across creators and institutions, as well as consistency in content quality and theme.